2017
DOI: 10.4236/msa.2017.83017
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low Temperature Synthesis of KNN Nanoparticles by Facile Wet Chemical Method

Abstract: Sodium potassium niobate (KNN) (K 0.5 Na 0.5 NbO 3 ) nanopowder with a mean particle size of about 20 -30 nm was synthesized by wet chemical route using Nb 2 O 5 as Nb source. A solution of K, Na and Nb cations was prepared, which resulted in a clear gel after the thermal treatment. Phase analysis, microstructure and morphology of the powder were determined by X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The obtained gel was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…A similar result, in terms of low calcination temperature, was obtained by Stavber and co‐authors, which produced pure KNN (K:Na = 1) starting from ammonium niobium oxo‐tris(oxalate) monohydrate and potassium and sodium nitrate . Recently, also Rani et al synthesized K 0.5 Na 0.5 NbO 3 powders by sol‐method but, at the same temperature of calcination of 500 °C, the final product showed a lower crystallinity (average size domain extension ≈ 240 Å) accompanied by the presence of an undesired secondary phase (K 3 Nb 6 O 17 ) …”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…A similar result, in terms of low calcination temperature, was obtained by Stavber and co‐authors, which produced pure KNN (K:Na = 1) starting from ammonium niobium oxo‐tris(oxalate) monohydrate and potassium and sodium nitrate . Recently, also Rani et al synthesized K 0.5 Na 0.5 NbO 3 powders by sol‐method but, at the same temperature of calcination of 500 °C, the final product showed a lower crystallinity (average size domain extension ≈ 240 Å) accompanied by the presence of an undesired secondary phase (K 3 Nb 6 O 17 ) …”
Section: Resultssupporting
confidence: 73%
“…In the left side micrograph (Figure A), the surface of the post‐heated gel shows the clear presence of pores ascribable to the release of CO 2 gas during the annealing process. The CO 2 evolution is a consequence of the thermal decomposition of the complex oxalates formed through the gelation, as it was already observed by Yao et al and further confirmed by Rani and coauthors . Upon compaction and subsequent annealing at 500 °C, the surface morphology of the final pellet changes with respect to the un‐treated powders.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The Williamson-Hall analysis relies on the principle that the approximate formula for the size broadening and the strain broadening vary quite differently with respect to the Bragg angle [19]. The crystallite size and strain can be obtained from the intercept at y-axis and the slope of line, respectively.…”
Section: Pxrd Analysismentioning
confidence: 99%
“…The negative slope 4ε ofFigure 4indicates that micro-strains cannot be a dominant source of broadening or proves that the strain is compressive while positive value indicates an expansion of the strain[29]. The low values indicate the occurrence of lattice relaxation within nanocrystallites[19]. The nonlinearity between βcosθ and sinθ can be due to low crystallized powder samples[29].Microscopy investigation shows large sized spherical grains that may have grown from the coalescences of small particles.…”
mentioning
confidence: 99%